2022
DOI: 10.1021/acs.nanolett.2c03456
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Pulse Generation with Binary Phase Control in Nonlinear InAs Metasurface

Abstract: The effect of terahertz (THz) pulse generation has revolutionized broadband coherent spectroscopy and imaging at THz frequencies. However, THz pulses typically lack spatial structure, whereas structured beams are becoming essential for advanced spectroscopy applications. Nonlinear optical metasurfaces with nanoscale THz emitters can provide a solution by defining the beam structure at the generation stage. We develop a nonlinear InAs metasurface consisting of nanoscale optical resonators for simultaneous gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…In addition to THz detectors, semiconductor metasurfaces also have the potential to be a new, versatile platform for THz generation where the THz field strength, polarity and spatial beam structure can be tailored through intelligent design of the metasurface [14][15][16] . Recently, we have demonstrated that both GaAs and InAs metasurfaces can be used to generate THz radiation 14,17 . In particular, an InAs metasurface can generate THz radiation via optical rectification with greater efficiency than a ZnTe crystal.…”
Section: Metasurface Thz Sources For Near-field Systemsmentioning
confidence: 99%
“…In addition to THz detectors, semiconductor metasurfaces also have the potential to be a new, versatile platform for THz generation where the THz field strength, polarity and spatial beam structure can be tailored through intelligent design of the metasurface [14][15][16] . Recently, we have demonstrated that both GaAs and InAs metasurfaces can be used to generate THz radiation 14,17 . In particular, an InAs metasurface can generate THz radiation via optical rectification with greater efficiency than a ZnTe crystal.…”
Section: Metasurface Thz Sources For Near-field Systemsmentioning
confidence: 99%
“…12,14 In the context of THz applications, metasurfaces can be employed to control the amplitude and phase of optical pulses, which can then be rectified to produce THz radiation. 12 However, due to their planar nature (i.e., a few hundred nanometers thickness), the interaction length is limited and mechanisms to enhance the optical-to-THz conversion efficiency are needed. 7,24 Despite the large increase of the nonlinear response due to optical phonon modes, the strong intrinsic absorption associated with this band has so far hindered the experimental observation of efficient optical-to-THz conversion in bulk LN crystals above 4 THz.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this perspective, solid-state THz source technologies that are being developed have the potential to fulfill several of the aforementioned requirements. Among them optical rectification of femtosecond laser pulses in nonlinear crystals has shown the ability to achieve high-intensity and broadband THz radiation, while nanoscale structures have the potential of providing miniaturized configurations of THz devices. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the recently established spintronic emitters show promise in the ongoing endeavor of actively controlling THz radiation. To date, these emitters have exhibited binary phase control and polarization manipulations, enabling polarization switching, beam steering, and lensing. Another nanoscale approach on the generation of tailored THz emission is based on the utilization of nonlinear metasurfaces (NLMSs). More precisely, the irradiation of plasmonic metasurfaces with femtosecond laser pulses in close vicinity to their localized surface plasmon resonance induces strong single-cycle THz emission due to optical rectification. , Interestingly, the recent expansion of the Pancharatnam–Berry phase (also called geometric phase) in the THz emission process from metasurfaces has aided in obtaining continuous spatial control over the emission phase . This was shown to demonstrate a variety of functional THz emitters .…”
Section: Introductionmentioning
confidence: 99%